The Relative Merits and Implications of Inflation Targeting for South Africa - Jonsson, Gunnar (IMF Working Papers; Working Paper ;, 1999)
This paper describes the main elements of inflation targeting, reviews its pros and cons, and examines the experiences thus far in countries using this framework. It discusses the implications and relative merits of such a framework for South Africa, and concludes that it would be feasible and desirable for South Africa to adopt explicit inflation targeting. Doing so could reduce uncertainties about the Reserve Bank's objectives and enhance the transparency of monetary policy. However, further experience with the operational aspects of the repurchase system and a refinement of the inflation forecasting framework may be needed before inflation targeting is implemented.